Ridiculus sum : le ridicule dans Madame Bovary - Juliette Azoulai (Flaubert: Revue Critique et Génétique, 2016)
The first scene in Madame Bovary shows a ridiculed character as he enters school. Many other episodes of the novel present ridicule’s sociological and psychological mechanisms through multiple variations: unseen ridicule, pinpointed ridicule, fear of the ridicule, conscious or unconscious ridicule. By following these various occurrences we intend to reveal the genealogy of ridicule offered by Flaubert. In this manner the novel deconstructs the principle of “relative ridicule”, substituting it with that of “ridicule inherent to human life” or “sad grotesque”.